Automatic stabilizers: A European Union design perspective - Shi, Haoran (Université d'Ottawa | University of Ottawa, 2018)
This paper aims to investigate the effect of the criteria proposed by the Maastricht Treaty and the Stability and Growth Pact (SGP) on the effectiveness of automatic stabilizers in the European Union (EU) member states. Using balanced panel data from 1960 to 2016, this paper relies on a reduced form model to estimate the effectiveness of the automatic stabilizers, employing a three stage least square model. The cyclical components of the government budget reflect the stabilizing ability, primarily stemming from the expenditure side. The EU design causes the structural breaks in the behaviour of the automatic stabilizers of the member states prior to and after the adoption of the explicit requirements in the Maastricht Treaty, while some EU member members exhibited such a change since the beginning of the European Monetary System (EMS). In addition, the requirements on the government debt-to-GDP ratio limit the use of the automatic stabilizers in the EU member states. Lastly, several theoretical extensions of the automatic stabilizer concept are analyzed in the EU context.